A Descriptive Analysis of EtOH Intoxication in our Latino Trauma Patients: An Indication for a Preventive Program. Issue 2 (March 2018) - Kopatsis, Anthony; Wagner, Christine; Costello, Helen; Morin, Nicholas; Kopatsis, Katherine Elizabeth; Gomez, Mario
Abstract : We sought to determine patterns of injury in our Latino trauma community targeting alcohol (EtOH) intoxication as an influential variable. With the information gained in our culturally specific and culturally sensitive trauma community, we can use the information to fine-tune our trauma preventive medicine programs. Trauma injuries are the third largest contributor to racial disparities in the United States. Alcohol is involved in approximately half of all trauma admissions to trauma centers around the country. Some investigators have shown that Latinos have higher rates of high-risk drinking, and this factor is independently associated with mortality after trauma. This study is a retrospective review of 524 Latino blunt and penetrating trauma admissions for years (2012–2014). Electronic medical records with the hospital trauma registry charts were evaluated. The trauma registry database included age, gender, EtOH, mechanism of injury, location, insurance, and disposition. Statistical significance was used with chi–square test. Our results show a predominantly male population with falls being the primary mechanism of injury. Intoxicated injuries occurred mostly at bars/clubs, but a substantial amount occurred at the workplace. Despite having a majority of the injuries occurring with patients that have Medicaid or Charity Care insurance, a certain amount of the alcohol-related injuries had private insurance. Many of our Latino trauma patients are still suffering from trauma-related EtOH intoxication. With the information obtained from our project, we will be able to fine-tune and target our trauma preventive medicine program to provide education for our inner-city Latino community of EtOH intoxication-related trauma injuries.